Optical waveguide devices, elements for making the devices and methods of making the devices and elements - MARCHEGIANO; JOSEPH E; BOOTH; BRUCE L (1994)
A substantially dry method for making an optical waveguide device with at least one buried channel waveguide in a laminated and hardened matrix. The method begins with exposing to light a region of a substantially dry photohardenable film adhered to a support. Then a first substantially dry photohardenable layer which is adhered to a support is laminated to one side of the film. Then the support is removed from the film. Then a second substantially dry photohardenable layer which is adhered to a support is laminated to the other side of the film. Then the layers and film are hardened.